Green Business: Strategy and Economic Feasibility in Environmentally Conscious Business Implementation - Maimuna; Abdur Rohman (ORGANIZE: Journal of Economics, Management and Finance, 2025)
As global awareness of sustainability increases, the concept of green business has become a major focus in the modern business world. This study discusses strategies for implementing environmentally conscious businesses and their long-term viability. By employing approaches such as the use of sustainable energy, circular economy-based waste management, and the use of green technology, companies can achieve a balance between profitability and ecological responsibility. Through a business feasibility analysis, this study evaluates various factors influencing business sustainability, including investment costs, market potential, and government policies and incentives that encourage the growth of sustainable green businesses. Case studies of companies that have successfully implemented sustainable business models demonstrate that innovation in environmentally friendly businesses not only reduces negative impacts on the environment but also provides higher economic value and competitiveness. Thus, green business is not just a trend, but a strategy that supports both business sustainability and environmental sustainability.